Transforming growth factor beta (TGFβ1) in breast milk and indicators of infant atopy in a birth cohort. Issue 3 (13th February 2014) - Joseph, Christine L. M.; Havstad, Suzanne; Bobbitt, Kevin; Woodcroft, Kimberley; Zoratti, Edward M.; Nageotte, Christian; Misiak, Rana; Enberg, Robert; Nicholas, Charlotte; Ezell, Jerel M.; Ownby, Dennis R.; Johnson, Christine Cole
Abstract Background The infant gut's ability to suppress immunologic reactions to food proteins could be influenced by levels of TGFβ in breast milk. We hypothesized that lower levels of TGFβ1 in the breast milk (BM) of mothers in the WHEALS birth cohort are associated with atopy at infant age 2–3 yrs. Methods We used data collected during infancy in addition to the results of skin prick tests (SPT+) and measures of specific IgE >0.35 IU/ml (spIgE) to milk, egg, and peanut at infant age 2–3 years. Infants were classified as food allergic (FA) based on parental report of infant symptoms/diagnoses and information from clinical assessments. Results Data for 304 cohort members were analyzed. Among non‐black infants, BM‐TGFβ1 was lower for those classified as FA (vs. no FA) and those SPT+ (vs., SPT‐), geometric mean = 1100 pg/ml vs. 1417pg/ml, p = 0.081; and 1100 pg/ml vs. 1415pg/ml, p = 0.064, respectively. Among infants of non‐atopic mothers, BM‐TGFβ1 was lower for those with elevated (vs. not elevated) sIgE, geometric mean = 1347 pg/ml vs. 1651 pg/ml, p = 0.047. Using logistic regression, adjusted odds ratios describing the association of BM‐TGFβ1 to the presence of atopic indicators in the infant were in the hypothesized direction only for non‐black infants of non‐atopic mothers: aORs for FA, sIgE and SPT+ were 0.08, 0.34, and 0.26 respectively; p = 0.091, 0.13, and 0.23. Conclusion Immune benefit of BM‐TGFβ1 could inform prevention strategies. Evidence of an association appears greatly influenced by infant race and maternal atopy. More research can determine if these relationships represent a modifiable risk factor for the development of food allergy in certain subgroups.